Thermodynamics for engineers - Kroos, Kenneth A.; Potter, Merle C. (Cengage Learning, 2015)
Presents a core course for disciplines in all four year engineering schools. This title helps Chemical and Biomedical engineering students to take courses in thermodynamics.